Market concentration in the banking sector: Evidence from Albania - Arjan Tushaj (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2010)
The market structure can be described by concentration ratios based on the oligopoly theory or the structure - conduct - performance paradigm. Measures of concentration and also competition are essential for banks conduction in the banking industry. Several researchers have proved concentration level to be major determinants of banking system efficiency. Theoretical characteristics of market concentration measures are illustrated with empirical evidence. The market structure of the Albanian Banking Sector has changed dramatically in recent years. On 1990s, our country has experienced deregulation, foreign bank penetration, and an accelerated process of consolidation and competition in the banking sector. Particularly, the working paper examines the nature and the extent of changes in market concentration of Albanian banking sector. It focused primarily on a descriptive and dynamic analysis of change in the concentration indices in banking sector from year to year. Also it examines how the inherited structure of the banking system affects the way of the distribution of market shares amongst the different banks that comprise on the banking sector.
Keywords: A20; G00; 330; Bank Concentration; Concentration ratios; HHI index; Market Structure; Bank; Marktstruktur; Wirtschaftskonzentration; Albanien